2017
DOI: 10.1080/10717544.2016.1259371
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo investigation for optimization of niosomal ability for sustainment and bioavailability enhancement of diltiazem after nasal administration

Abstract: Diltiazem hydrochloride (DTZ) is a calcium channel antagonist depicted by extensive first pass metabolism and low oral bioavailability. The aim of this work was to develop niosomes for potential nasal delivery of DTZ. Niosomes protect hydrophilic drugs inside their core while nasal route offers both rapid onset and evasion of first-pass metabolism. Niosomes were prepared using a combination of Span 60 or Brij-52 with cholesterol (CHOL) in different molar ratios followed by determination of entrapment efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Niosomes have larger PS so they show lower PDI. On the other hand, spanlastics which have smaller PS show larger PDI that may be due to the difference in composition between both types of vesicular structures [33].…”
Section: The Effect Of Independent Formulation Variables On the Polydmentioning
confidence: 99%
See 1 more Smart Citation
“…Niosomes have larger PS so they show lower PDI. On the other hand, spanlastics which have smaller PS show larger PDI that may be due to the difference in composition between both types of vesicular structures [33].…”
Section: The Effect Of Independent Formulation Variables On the Polydmentioning
confidence: 99%
“…While the spanlastics showed lower EE than niosomes this may refer to the presence of span 60 and absence of cholesterol. Span 60 has a low HLB value (5.3), long carbon chain (C16) and it has a high phase transition temperature which decreases the leakage and the fluidity of the bilayer that leads to lower EE [33,37].…”
Section: The Effect Of Independent Formulation Variables On Entrapmenmentioning
confidence: 99%
“…Intranasal folic acid niosomes intended for brain targeting have shown controlled ex vivo perfusion [147]. Regarding the systemic effects of intranasal niosomes, diltiazem-loaded niosomes have shown high half-life (T1/2 ) and enhanced AUC 0-∞ with a reduced elimination rate; such prolonged action for diltiazem is of great value compared to its low oral bioavailability due to extensive first-pass metabolism [148]. The study of using intranasal niosomes for vaccination with glycoprotein B of herpes simplex virus type 1 has shown in vitro controlled release and in vivo elicited plasma glycoprotein antibodies (IgG) and systemic T helper cells [149].…”
Section: Niosomesmentioning
confidence: 99%
“…Studies showed that zidovudine (BCS Class III) niosomes prepared with Tween 80 as surfactant and DCP as stabilizer (-ve charge-inducer) effectively entrapped high amounts of drug and released 88.72% of drug over 12 h [13]. Ammar HO et al investigated that Diltiazem (BCS Class I) niosomes prepared with span 60 and Cholesterol (1:1 molar ratio) showed maximum entrapment efficiency and drug release on in-vitro investigation and in-vivo study exhibited an increase in MRT, t1/2 and AUC with a decrease in Ke [14].…”
Section: Choice Of Surfactant and Stabilizermentioning
confidence: 99%